Human Bone Marrow Mesenchymal Stem/Stromal Cells Preserve Their Immunomodulatory and Chemotactic Properties When Expanded in a Human Plasma Derived Xeno-Free Medium - A. Blázquez-Prunera; C. R. Almeida; M. A. Barbosa (Stem Cells International)
Due to their immunomodulatory and chemotactic properties, hMSC are being explored to treat immune-related diseases. For their use in human therapies, it is necessary to culture hMSC in xeno-free conditions. In this study, the impact that a xeno-free medium based on a human plasma derivate has on these properties was analysed. Bone marrow-derived hMSC preserved their immunosuppressive and immunostimulatory properties, as observed with in vitro assays with hMSC cocultured with mixed leukocyte reactions or with mitogen-stimulated leukocytes. Moreover, hMSC expanded in xeno-free medium were recruited by macrophages in both migration and invasion assays, which indicates that the cells maintained their chemotactic properties. These data suggest that xeno-free expanded hMSC preserved their immunomodulatory and chemotactic properties, indicating that the described xeno-free medium composition is a potential candidate to culture and expand hMSC for human cell therapies.